Psychometric properties, factor structure, and German population norms of the multidimensional fatigue inventory (MFI-20) - Westenberger, Adrian; Nöhre, Mariel; Brähler, Elmar; Morfeld, Matthias; de Zwaan, Martina (Frontiers in Psychiatry, 2022)
Objective The Multidimensional Fatigue Inventory (MFI-20) is commonly used, but its factor structure remains unclear. The MFI-20 consists of five subscales (general fatigue, physical fatigue, reduced activity, reduced motivation, and mental fatigue). This study investigates the psychometric properties, including the factor structure, of a general German population sample and tests group hypotheses on gender and age. Another objective is to provide normative data by gender and age groups. Methods Using data from a representative German sample (n=2,509), reliability and convergent validity measures, group hypothesis testing, and confirmatory/exploratory factor analyses were conducted. Results The MFI-20 demonstrated satisfactory internal consistency and showed adequate convergent validity with the SF-36. All subscales of the MFI-20 were significantly correlated (0.71–0.85). Physical fatigue exhibited the highest (0.42) and mental fatigue had the lowest (0.19) correlation with age. Fatigue scores were significantly higher for women and significantly increased with age. A five-factor structure showed poor model fit; using an exploratory factor analysis, a two-factor structure emerged (a general factor and a mental/motivational factor). Conclusion The MFI-20 is a reliable and valid instrument for measuring fatigue in the general population, but the five-factor structure is not supported. The subscale general fatigue or the MFI-20 total score might measure fatigue sufficiently. The provided norms can be used for further research and individual assessment.